A brief exploration of fog computing architecture, technologies and challenges - Challa, Ramaiah; Kiran Kumar, K (International Journal of Engineering and Technology, 2018)
Now a dayâ€™s IoT systems are being used in rapid rate, so much data is being generated byÂ  massive ubiquitous things handling of that much data is not a simple issue it very critical task. Then again, despite the fact that that distributed computing has filled in as an efficient approach to process and store these information, in any case, challenges, for example, the expanding requests of ongoing or dormancy delicate applications and the impediment of system data transfer capacity, still can't be tackled by utilizing just cloud computing. Accordingly, another computing known as fog computing was proposed as extension of cloud computing. It brings the cloud services that are communication, computation and storage near to edge devices and users so latency can be reduced. In this papers details of fog computing are discussed.